The effect of cladribine on immunoglobulin levels compared to B cell targeting therapies in multiple sclerosis. Issue 1 (January 2023) - Lycett, Mitchell J; Lea, Rodney A; Maltby, Vicki E; Min, Myintzu; Lechner-Scott, Jeannette
Background: Cladribine is a useful therapeutic option in RRMS with moderate to high disease activity. Its oral formulation and tolerability make it a useful alternative to infusion therapies. Cladribine is known to deplete CD19 + B lymphocytes, but its effect on immunoglobulin subsets is unclear. Objective: To identify whether cladribine therapy in pwMS reduces immunoglobulin subset levels as a surrogate marker of infection risk. Methods: A 'real-world' retrospective analysis of 341 pwMS presenting to a single tertiary centre between March 2017 and July 2021. Differences in immunoglobulin levels between cladribine, other disease-modifying therapies and no active treatment were assessed using a univariate ANOVA. Results: Three hundred and forty-one patients had immunoglobulin levels assessed, with 29 patients treated with cladribine. The mean IgG, IgM and IgA levels on cladribine therapy were 10.44 ± 0.40, 0.99 ± 0.09 and 2.04 ± 0.18 g/L respectively. These were not significantly different from patients not on active treatment. There was a statistically significant reduction in IgG and IgM levels for patients treated with ocrelizumab (9.37 ± 0.19 and 0.68 ± 0.04 g/L) and natalizumab (8.72 ± 0.53 and 0.69 ± 0.12 g/L) compared to patients not on treatment. Conclusion: Cladribine therapy for RRMS was not associated with immunoglobulin subset deficiencies. This is contrasted to ocrelizumab and natalizumab which demonstrate significant reductions in both IgG and IgM levels.